Doppler Impedance Changes at the Fetal Brain Vessels in a Pregnancy Affected with a Multiple Combination of Uteroplacental Anomalies. (28th February 2012) - Morales-Roselló, José; Peralta Llorens, Núria
Abstract : A fetus with a very rare five-fold combination of uteroplacental anomalies, bicornuate uterus, short cervix with cervical incompetence, multilobed placenta succenturiata, accessory cotyledon within the cervical funneling, and umbilical cord insertion into the anomalous cervical cotyledon, presented an early and marked decrease at the vertebral and middle cerebral arteries Doppler resistances. This cerebral low-impedance state, usually found before labor, and considered an adaptive mechanism developed to protect the fetus at term from labor asphyxia, was present for an unknown reason at 20 weeks. After the patient was treated with vaginal progesterone, the cervix shortening improved and markedly, at the same time, the cerebral vascular resistances increased and maintained an adequate for gestational age impedance until delivery at 34 weeks. As the described uteroplacental anomalies determined a high risk of preterm delivery, due to cervical dilation, cord compresion, and placental haemorrhage, these fluctuating brain vascular changes might be the result of the fetal adaptation to the changes preceding an imminent delivery.